Monitored control of Marssonina blotch of apple caused by Marssonina coronaria - ANIL KUMAR*, ANIL KUMAR* (Indian Phytopathology, 2014)
Protective and curative activity of mancozeb, dodine, metiram, carbendazim, thiophanate-methyl, Shield, kresoxim methyl, pyraclostrobin + metiram (Cabrio top) and difenoconazole against Marssonina blotch of apple, caused by Marssonina coronaria was determined under polyhouse and field conditions. Apple plants aged about two years (cv. Starking Delicious) were grown in pots for under polyhouse experiments and while 5-8 years old trees were used for field evaluations. Plants were sprayed to run off with aforementioned fungicides either before (protectant) and after infection (curative). The i-METO automatic weather monitoring equipments were installed for identifying infection periods of Marssonina blotch in apple in the orchard. Dithiocarbamates (mancozeb and metiram) showed best protective activity whereas, strobilurins (Cabrio top and kresoxim methyl) had strongest curative activity against the disease in polyhouse as well as under field conditions. Mancozeb registered 94.1 per cent disease control when applied before infection whereas, Cabrio top showed 91.1 per cent disease control when applied on the basis of occurrence of infection periods under field conditions